ANALISIS TINDAK TUTUR DI SERIAL TV: “GLEE” MUSIM KE-2 - AZIZAH, MAR ATUL (Jurnal Ilmiah Mahasiswa FIB, 2015)
Speech acts can be studied in any media, including TV series. Speech actshave several types. They are locutionary, illocutionary and also perlocutionaryacts. Locutionary act means the exact meaning of the peformed utterance. On the other hand, locutionary act can be part of illocutionary act if it forces the hearer to understand the hidden meaning or intention of the speaker. Perlocutionary act is the effect of the illocutionary act occured. However, Searle (1969) adds one more act that he argues is also important. That is a propositional act. It is an act of referring and predicating. For academic purposes, the writer is intrigued to study speech acts phenomena through TV series. This study has three problems to solve namely, 1) What are propositional acts found in the utterances of the selected episodes of Glee season 2?  2)What are illocutionary acts found in the utterances of the selected episodes of Glee season 2? 3)What  are perlocutionary acts found in the utterances of the selected episodes of Glee season 2? The writer uses a qualitative research method in terms of content analysis. The content analysis isapplied to analyze utterances that consist of speech acts (propositional, illocutionary, and perlocutionary) produced by Glee cast,specifically four maincharacters. The utterances are provided in the transcription of Glee’s four selected episodes. The writer finds 198 propositional acts out of 207 utterances. Not all utterances are propositional acts, because there are 9 predicating acts that stand alone. On the other hand, in illocutionary acts, representatives category stand out the most with 82 utterances. The least frequently used category in illocutionary acts is commissives. The writer only finds 23 types of commissives. The perlocutionary acts appears in most of utterances. Only 6 utterances do not consist of perlocutionary acts. The writer also recommends the future researchers to find other types of illocutionary acts that the writer can not find. Kata Kunci: tindak tutur, tindak lokusi, tindak proposisional, tindak ilokusi,tindak perlokusi, glee musim ke-2.